Developing English Instructional Design Based on Higher Order Thinking Skills (HOTS) at SMK IT Al-Qimmah - Saputra, Ari; Ilyani, Ria (Lembaga Yasin AlSys, 2022)
This research aimed at designing an English Instructional design based on higher-order thinking skills. The type of this research was research and development (R&D) which refers to Borg and Gall development model. The subject of this study was English teacher at the Al- Qimmah Integrated Islamic Vocational School in the school year 2021/2022. In terms of data collection techniques, the researcher used interview and questionnaires, while the data analysis techniques in this study are qualitative and quantitative. From the data analysis, the following results were obtained: Al-Qimmah Integrated Islamic Vocational School uses the 2013 curriculum, but the learning implementation plan used is still not based on higher-order thinking skills. To obtain valid data, a validation process is carried out by the validator on the developed learning implementation plan. Based on the results of the study, it can be concluded that the learning implementation plan meets the valid criteria with an average value of 4.5.